CSIG-27. DIFFERENTIAL ELEVATION OF TERT ACTIVITY AND SENSITIVITY TO TEMOZOLOMIDE BY TYPE OF TERT MUTATION IN MGMT PROMOTER-METHYLATED GLIOBLASTOMA. (5th November 2018) - Silginer, Manuela; Papachristodolou, Alexandros; Hentschel, Bettina; Gramatzki, Dorothee; Felsberg, Jörg; Löffler, Markus; Schackert, Gabriele; Westphal, Manfred; Tonn, Jörg-Christian; von Deimling, Andreas; Pietsch, Torsten; Reifenberger, Guido; et al.
Abstract: BACKGROUND: Benefit from temozolomide chemotherapy in glioblastoma is essentially limited to patients with tumors that exhibit O 6 -methylguanine DNA methyltransferase (MGMT) promoter methylation. Recent retrospective clinical analyses indicate that the impact of the MGMT status on chemosensitivity may be modulated by telomerase reverse transcriptase (TERT) promoter mutations. These commonly affect two regions of the TERT promoter, C228T and C250T. METHODS: TERT promoter mutation status and TERT activity were determined and correlated with sensitivity to irradiation or temozolomide in long term and glioma-initiating cell lines. TERT status alterations were induced using sh-mediated gene TERT silencing or wildtype TERT overexpression. TERT mutation and MGMT promoter methylation status were also determined in a clinical patient cohort from the German Glioma Network. RESULTS: C228T-mutant glioma cell lines (n=8) show higher TERT mRNA expression (mean 0.046 ± 0.012 vs 0.012 ± 0.004 arbitrary units, p=0.049) and higher TERT catalytic activity (mean 122 ± 16 vs 53 ± 11 arbitrary units, p=0.022) than C250T-mutant glioma cell lines (n=5). C228T-mutant glioma cell lines are also more sensitive to irradiation (mean ED90 4.6 ± 0.7 versus 7.1 ± 0.8 Gy, p=0.039) or temozolomide (mean EC50 101.6 ± 58.5 versus 295.2 ± 53.8 µM, p=0.045) in vitro . Targeted alterations of TERT status affect sensitivity to irradiation or temozolomide: TERT gene silencing confers protection whereas TERT overexpression confers sensitization. Consistent with these preclinical observations, patients with C228T TERT mutation and MGMT promoter methylation may derive more benefit from temozolomide chemoradiotherapy (median overall survival 26.5 months, 95% CI 20.3–32.7) than patients with the C250T mutation (median overall survival 16.2 months, 95% CI 8.5–23.8) or patients without TERT mutation (median overall survival 23.7 months, 95% CI 18.7–28.8). CONCLUSIONS: These results confirm a link between TERT promoter status and sensitivity to irradiation and temozolomide and illustrate how TERT and MGMT might interact to determine outcome in human glioblastoma. They allow to design future targeted interventions focusing on TERT and MGMT to improve the treatment of glioblastoma.